The socio-emotional development of preschoolers: a case study - Mejah, Hafizah; Abu Bakar, Abu Yazid; Amat, Salleh (Universitas Negeri Padang, 2019)
The objective of this study is to look at the socio-emotional developmental stages of preschool children. The study has been conducted in two preschool classes of Sekolah Kebangsaan King George V, Seremban, Negeri Sembilan, Malaysia. The data collection has been done via a survey questionnaire that has been administered tofifty preschoolers observed in both classes. Data collected was descriptively and inferentially analyzed using Statistical Package for Social Sciences (SPSS) software version 20.0. The main findingrevealthat the repondents’ psycho-socio-emotional development is equivalent among genders, as well as between the age of five and six years old. This initial information would help teachers to affectively prepare the guidance programme for these preschoolers when they enter elementary classes.